1956
DOI: 10.1103/physrev.104.699
|View full text |Cite
|
Sign up to set email alerts
|

Prompt Gamma Rays Accompanying the Spontaneous Fission ofCf252

Abstract: 699 event were of high energy. A subsequent investigation employing apparatus primarily designed to measure electron velocity spectra is contemplated. Such spectra are of interest because according to the Weizel-Beeck theory of ionization by ions, a quasi molecule is formed during an ionizing collision, and it seems likely that the 1 M. Deutsch and J. Rotblat, Atomic Energy Commission Report .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1962
1962
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…As another point of comparison, Smiuh et al [2] estimated that there were 5.0 gammas per fission between 0.5 and 2.3 MeV. We can estimate from Table I We turn now to the work of Ramamurthy et al, [12] In the present work, this has been found to be a serious source of bias if not properly adjusted.…”
Section: Review Of Relevant Literaturementioning
confidence: 62%
See 3 more Smart Citations
“…As another point of comparison, Smiuh et al [2] estimated that there were 5.0 gammas per fission between 0.5 and 2.3 MeV. We can estimate from Table I We turn now to the work of Ramamurthy et al, [12] In the present work, this has been found to be a serious source of bias if not properly adjusted.…”
Section: Review Of Relevant Literaturementioning
confidence: 62%
“…For example, the threshold for the first entry (Smith) [2] was inferred approximately from the remark that a small photopeak was detected near 60 keV. The threshold for the second entry was inferred from the left-hand-most point in Figure 6 of Refer¬ ence 3.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Isotopic sources also produce photons: 252 Cf produces ~10 Ȗ/n [7] and AmBe produces ~0.6 Ȗ/n from fission [8]. An AmBe source also produces many lower energy photons from the natural decay of Am; these photons are not associated with neutron production.…”
Section: Gamma Spectrum and Intensitymentioning
confidence: 99%